‏A Silent Storm: A Narrative Review of Systemic Manifestations of Odontogenic Infections and a Framework for Interdisciplinary Recognition from Pre-Hospital Care to Rehabilitation - Hakami, Ehsan Ali Mohammed; Hakami, Nisrin Ali Mohammed; Kuriri, Afnan Hadi; Makin, Ghaliah Hadi Mohammed; Aldosari, Fahad Mohammed Bereik; Alanazi, Ashwaq Jaloud; Aldosari, Amer Mohamed Abdollah; Aldosari, Safi Saad Abdullah; Aldawsari, Mohammed Mubarak Abdullah; Aldawsari, Saeed Abdullah; Alkhebri, Hanaa Ibrahim Essa; Aldawsari, Obaid Abdulaziz Saeed; et al. (Saudi Journal of Medicine and Public Health, 2024)
Background: Odontogenic infections can progress from dental structures to cause severe, life-threatening systemic complications. These conditions represent a critical intersection of dental, emergency, critical care, and rehabilitation medicine, yet physical therapists' role in this continuum remains underrecognized. Aim: This narrative review synthesizes evidence on the pathophysiology, recognition, and interdisciplinary management of severe systemic complications from oral infections, proposing an integrated framework for early detection and rehabilitation from paramedic contact through ICU to physical therapy. Methods: A comprehensive literature search was conducted across PubMed, Scopus, and CINAHL (2010-2024). Included studies focused on epidemiology, management, and rehabilitation of severe odontogenic infections with systemic spread. Results: The review delineates infection pathways, identifies clinical red flags, and highlights rehabilitation needs. Two original frameworks are presented: a pre-hospital screening tool for paramedics/nurses and an integrated rehabilitation protocol incorporating physical therapy. Conclusion: Effective management demands seamless collaboration between all involved professions, including physical therapy for functional recovery. Standardized interdisciplinary protocols can significantly reduce morbidity and mortality while optimizing long-term outcomes.